Isokinetic leg-press power-force-velocity profiles are reliable in male and female elite athletes but not interchangeable with vertical jump profiles - Fessl, I.; Dirnberger, J.; Kröll, J.; Wiesinger, H.-P. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To evaluate the test-retest reliability of isokinetic leg-press power-force-velocity profile (P-F-v) parameters in male and female elite athletes. In addition, we determined the concurrent validity of leg-press against squat-jump (SJ) P-F-v parameters in task-experienced athletes.